(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper compares different Boundary Element Method (BEM) solvers used to calculate hydrodynamic effects on floating bodies to reveal divergence in their calculations due to different modeling conventions. These differences become evident when analyzing different wave headings, multiple bodies, or non-axisymmetric floating bodies, i.e., situations where the pose, orientation, and position of the body with respect to the global reference frame and coordinate frame will influence the hydrodynamics calculations. BEM-based solvers use the Linear Potential Flow Theory (LPFT) which is a common midfidelity modeling approach for offshore floating structures. In this work we show that there is a lack of consensus in the commonly used BEM solvers, viz., WAMIT, Capytaine, NEMOH, AQWA, HAMS, and OrcaWave. We demonstrate the differences in hydrodynamic coefficients calculated by different BEM solvers by considering two triangular prisms. The available documentation for the BEM solvers at the time of writing, along with communications with the developers of these BEM solvers left some ambiguities. However, this work was able to reverse-engineer the cause for the differences in the results in a systematic manner. Furthermore, this work presents mathematical expressions that can convert hydrodynamic coefficients from each of the considered BEM solvers so as to enable verify of the hydrodynamic calculations across different BEM solvers. Finally, the findings were implemented in BEMRosetta (https://github.com/BEMRosetta/BEMRosetta) so that the general community can easily convert or verify their hydrodynamic calculations.